The Population-Based Risk of Need for Coronary Revascularization According to the Presence of Type 2 Diabetes Mellitus and History of Coronary Heart Disease in the Korean Population - Jung, Chang Hee (PLoS One, 2015)
BACKGROUND: Whether diabetic patients without a history of coronary heart disease (CHD) have the same risk of CHD events as non-diabetic patients with a history of CHD remains controversial. This study aimed to determine whether type 2 diabetes mellitus (T2DM) is a coronary heart disease (CHD) equivalent in the need for coronary revascularization procedures (RVs) in the Korean population. METHODOLOGY/PRINCIPAL FINDINGS: We followed 2,168,698 subjects who had oral anti-diabetic drugs (OADs)-taking T2DM in 2008 and/or CHD in 2007–2008 (i.e., recent CHD). We used systematic datasets from the nationwide claims database of the Health Insurance Review and Assessment service of Korea, which is representative of the whole population of Korea, from January 2007 to December 2012. The primary study endpoint was the development of need for RVs (i.e., incident CHD) after January 2009 among three groups based on their status of T2DM and recent CHD, i.e., T2DM only, recent CHD only, and both T2DM and recent CHD. After adjustment for age and sex, patients with recent CHD only had 2.14 times the risk of incident CHD (95% CI, 2.11–2.18, P<0.001) compared with patients with T2DM only. Patients with both T2DM and recent CHD demonstrated approximately 2-fold increased risk of incident CHD compared with subjects with recent CHD only (95% CI, 1.75-1.82), while 4-fold increased risk compared with subjects with T2DM only (95% CI, 3.71-3.87). The risk of incident CHD also differed according to sex and age. CONCLUSIONS/SIGNIFICANCE: This analysis of data from the nationwide claims database revealed that T2DM did not have a recent CHD equivalent risk in the Korean population. These results suggest that an appropriate strategy for the CHD risk stratification in diabetic patients should be adopted to manage this population.